Functional roles and mechanisms of ginsenosides from Panax ginseng in atherosclerosis - Xue, Qianqian (J Ginseng Res, 2021)
Atherosclerosis (AS) is a leading cause of cardiovascular diseases (CVDs) and it results in a high rate of death worldwide, with an increased prevalence with age despite advances in lifestyle management and drug therapy. Atherosclerosis is a chronic progressive inflammatory process, and it mainly presents with lipid accumulation, foam cell proliferation, inflammatory response, atherosclerotic plaque formation and rupture, thrombosis, and vascular calcification. Therefore, there is a great need for reliable therapeutic drugs or remedies to cure or alleviate atherosclerosis and reduce the societal burden. Ginsenosides are natural steroid glycosides and triterpene saponins obtained mainly from the plant ginseng. Several recent studies have reported that ginsenosides have a variety of pharmacological activities against several diseases including inflammation, cancer and cardiovascular diseases. This review focuses on describing the different pharmacological functions and underlying mechanisms of various active ginsenosides (Rb1,-Rd, -F, -Rg1, -Rg2, and -Rg3, and compound K) for atherosclerosis, which could provide useful insights for developing novel and effective anti-cardiovascular drugs.